Effects of Bee Bread on Male Reproductive System of Sprague Dawley Rat - Mohd Nizam, Haron; Fatimah Hamizah, Zakaria (2018)
Bee bread has been traditionally consumed for enhancement of male fertility. There has been an increasing demand for natural products, particularly the bee products. However, to date, the role of bee bread and its underlying potential mechanism for protecting or improving sperm parameters has not been reported. Therefore, this study determines the role of bee bread supplementation on male reproductive organ weight and sperm parameter in adult male rat. There are two groups which consist of treated and control group with 6 male rats in each group. The control rats were administered with 1ml of distilled water, while the treated rats were administered with 0.5g/kg body weight of bee bread (diluted in 1 ml of distilled water) for 28 days. At the end of experiment, rats were euthanised, and reproductive organs weight were collected and weighed. Cauda epididymis was collected for sperm count and sperm morphology evaluations. Apart from the prostate gland, there is no significant difference observed between the mean weight of testis, seminal vesicle, epididymis of the control rat and the treated. In addition, there is no significant difference in sperm count and sperm morphology between the control group and treated group. The results of this study show that bee bread supplementation causes an increase in the weight of the prostate gland in adult rats.